2015
DOI: 10.1523/jneurosci.3817-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Myelin-Reactive Th17 Cells Impairs Endogenous Remyelination in the Central Nervous System of Cuprizone-Fed Mice

Abstract: Multiple sclerosis (MS) is a demyelinating disease of the CNS characterized by inflammation and neurodegeneration. Animal models that enable the study of remyelination in the context of ongoing inflammation are greatly needed for the development of novel therapies that target the pathological inhibitory cues inherent to the MS plaque microenvironment. We report the development of an innovative animal model combining cuprizone-mediated demyelination with transfer of myelin-reactive CD4 ϩ T cells. Characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 43 publications
7
80
0
Order By: Relevance
“…Furthermore, attenuation of brain T H 17 influx reduced white matter injury, limited brain atrophy, and prevented chronic functional deficits after neonatal hypoxia-ischemic injury [270]. These findings are in line with reports showing myelin-reactive T H 17 cells induced demyelination and impaired endogenous remyelination in pre-clinical white matter injury models and in multiple sclerosis patients [271276]. In addition, curcumin, a curry spice that we found to improve TBI outcomes [243], attenuated expression of RORγT, a transcription factor involved in T H 17 differentiation, decreased myelin basic protein-autoreactive T cells, and blocked the production of IL-17, the signature cytokine released by T H 17 cells, after EAE [277].…”
Section: Translational Implicationssupporting
confidence: 83%
“…Furthermore, attenuation of brain T H 17 influx reduced white matter injury, limited brain atrophy, and prevented chronic functional deficits after neonatal hypoxia-ischemic injury [270]. These findings are in line with reports showing myelin-reactive T H 17 cells induced demyelination and impaired endogenous remyelination in pre-clinical white matter injury models and in multiple sclerosis patients [271276]. In addition, curcumin, a curry spice that we found to improve TBI outcomes [243], attenuated expression of RORγT, a transcription factor involved in T H 17 differentiation, decreased myelin basic protein-autoreactive T cells, and blocked the production of IL-17, the signature cytokine released by T H 17 cells, after EAE [277].…”
Section: Translational Implicationssupporting
confidence: 83%
“…The injection of IL-4 treated MIGs in the CSF of EAE animal induced an increase of oligodendrogenesis in the spinal cord (Butovsky, 2006). In contrast, Th1 supernatants inhibit OPC differentiation in vitro (Moore et al , 2015) and transfer of enriched myelin-reactive Th17 cells impedes remyelination in a cuprizone model (Baxi et al , 2015). However, because cells were injected in the systemic compartment and not in the CNS parenchyma, the observed effects in the modulation of the remyelination process could be indirect.…”
Section: Discussionmentioning
confidence: 99%
“…In CX3CR1 deficient mice the clearance of myelin debris is abrogated, leading to improper remyelination [104]. A recent study demonstrated that myelin-reactive Th17 cells impair the endogenous remyelination process, possibly due to recruitment of pro-inflammatory peripheral monocytes [105]. Our unpublished data reveal that SOCS3 deficiency in myeloid cells results in a more severe and accelerated demyelination in response to cuprizone.…”
Section: Role Of Jak/stat Signaling In Innate Immunity In Neuro-inmentioning
confidence: 95%